2020
DOI: 10.24259/fs.v4i1.7442
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Being Political: Emergence of a Multi-stakeholder Forum at the Lake Malili Complex, South Sulawesi

Abstract: Multi-stakeholder forums are considered an essential element of landscape approaches for sustainable development and integrated ecosystem management. Such forums are widely adopted in environmental management policies and introduced as precursors for novel institutional arrangements for collective action in complex landscapes. However, while they are often held up as a mechanism for greater inclusion and representation, they can also further marginalize less powerful stakeholders. In this respect, the importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Although the cultural transmission framework discussed above offers compelling models and detail questions, it neglects the material and structural conditions such as changes in environment, political economy, and power relations, which are undeniably influential to cultural changes in community and their behavior (Harris et al, 2007). Recent researches have also shown that factors like political stability (Adebayo, 2022), technological innovation and environmental degradation (Adebayo et al, 2022), the possession of social capital (Carmen et al, 2022), as well as formal and informal decision making in the local level (Sirimorok & Rusdianto, 2020) determine changes in culture and society. In addition, the majority of literature around cultural transmissions use quantitative modeling in a large-scale population level (Mesoudi & Whitten, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the cultural transmission framework discussed above offers compelling models and detail questions, it neglects the material and structural conditions such as changes in environment, political economy, and power relations, which are undeniably influential to cultural changes in community and their behavior (Harris et al, 2007). Recent researches have also shown that factors like political stability (Adebayo, 2022), technological innovation and environmental degradation (Adebayo et al, 2022), the possession of social capital (Carmen et al, 2022), as well as formal and informal decision making in the local level (Sirimorok & Rusdianto, 2020) determine changes in culture and society. In addition, the majority of literature around cultural transmissions use quantitative modeling in a large-scale population level (Mesoudi & Whitten, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In some cases, collective action can translate simply into taking matters into their own hands (DeVore, 2019). Less powerful organized citizen groups need to be able to build sufficient power to level the playing field before diverse stakeholder resource management arrangements can achieve meaningful results for all parties Sirimorok & Rusdianto, 2020). Furthermore, studies also suggest that local citizens need to be able to negotiate among themselves to go beyond the essentialist 'community' point of view and create 'democratic spaces' for all, including those marginalized in the community (Agrawal & Gibson, 1999;Shaw, 2014).…”
Section: Sirimorok Et Al (2023)mentioning
confidence: 99%
“…The article by Sirimorok and Rusdianto (2020a) takes on directly the issue of governing scales at the village and district levels. They examine the opportunities for developing conservationoriented coalitions based on replicating successful localized cases.…”
Section: Conservation and Institutionsmentioning
confidence: 99%
“…Research from Maluku, for example, (Salampessy et al, 2017), highlights the flaws of social forestry policy applications for its overly formulaic solutions, as middlemen co-opted the process that led to the dispossession of forest cultivators to their groves of cloves. A number of the contributions to this special section also seek to explore these and other formally supported community-based or co-management arrangements, ranging from a close examination of local institutions and their practices related to conservation (Batiran and Salim, 2020;Sirimorok and Safriyanto, 2020b), or more explicit community conservation partnerships initiated and supported by the state and other partners to develop new models for managing forest and coastal/marine areas (Anugrahsari et al, 2020;Sirimorok and Rusdianto, 2020a;Sirimorok and Rusdianto, 2020b). Nevertheless, there is much more to be explored among these and other policy prescriptions for involving communities in conservation from across this vast region.…”
Section: Emerging Issues On Community Conservation In Wallaceamentioning
confidence: 99%